2020
DOI: 10.18502/ijps.v15i3.3814
|View full text |Cite
|
Sign up to set email alerts
|

The Most Stressful Events during the COVID-19 Epidemic

Abstract: Objective: Stressful events increase in traumatic conditions. Coronavirus is a new and serious challenge and significant public health problem, which can cause different stressors. This study has identified stressful events experienced by Iranian adults during the COVID-19 epidemic. Method: Data on stressful events during the COVID-19 epidemic were collected online from 418 adults (mean age 37.16 years; 57.4% female and 42.6% male) using quota sampling method. Epidemic Stressful Events Checklist was appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 31 publications
1
23
0
1
Order By: Relevance
“…Based on reviewing literature [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ] of the conceptual model of this study, the relationship between HL and COVID-19 anxiety level with modulating demographic variables of sex, age, history of chronic disease, history of COVID-19 and social support in adults living in Iran was investigated at the time of COVID-19 outbreak ( Figure 1 ).
Figure 1 Conceptual model.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on reviewing literature [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ] of the conceptual model of this study, the relationship between HL and COVID-19 anxiety level with modulating demographic variables of sex, age, history of chronic disease, history of COVID-19 and social support in adults living in Iran was investigated at the time of COVID-19 outbreak ( Figure 1 ).
Figure 1 Conceptual model.
…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of COVID 19 for reasons such as loss of income, feeling of loneliness and inactivity due to home quarantine, unpredictable consequences of the disease and uncertainty about its treatment, limited access to basic services, increasing alcohol use, reducing family and social support [ 2 ], the need to comply the obligation of social distance [ 3 , 4 , 5 ] and major changes in people's lifestyles, such as the need for using personal protective equipment (PPE) are subjects to high stress [ 6 , 7 ]. These stressors, along with other risk factors such as following the news of COVID-19, widespread rumors about the HL of the disease, and the onslaught of negative and inaccurate information in cyberspace may lead to anxiety associated with COVID-19 [ 8 ]. In addition to the above, COVID-19 anxiety may be related to various factors related to the cultural structure and health facilities of different communities that need to be identified and preventive measures in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…A fter one unprecedented year of coronavirus disease 2019 (COVID- 19), which was first emerged in Wuhan, China, stats show the impacts of the pandemic on over 85 million confirmed cases all around the world [1]. The growing number of over 79000 currently reported cases and over 15000 deaths in the last 24 hours showed that this public health scenario had not finished yet [1].…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy results from a meta-analysis of the psychological and mental impact of COVID-19 showed an increase in the prevalence of stress, anxiety, and depression among the general population during the COVID-19 pandemic [10,11]. As stated in Iran, anxiety [12], depression [13], posttraumatic stress disorder [14], obsessivecompulsive behaviors [15], substance abuse [16], suicidal ideation and attempts, and other symptoms of distress could be induced and/or exacerbated as a result of the various COVID-19-related factors such as fear, stress, anxiety, uncertainties, escalating number of mortalities [17], psychological impacts of the pandemic (such as the global economic recession [18]), increase of the prices of essential and healthrelated goods, decrease of the income, job loss [19], and the ongoing effects of sanctions and embargo [6,20,21]. Consequently, it was hypothesized that since other similar chronic stresses could induce serious physical, cognitive, and psychological symptoms [2], mental health deterioration was greater than expected; therefore, it would require more forceful measures.…”
Section: Introductionmentioning
confidence: 99%
“…The specific phobia belongs to anxiety disorders in the 5th edition of the Diagnostic And Statistical Manual of mental disorders (DSM-5). The fear or anxiety associated with the presence of a particular situation or object that can be recognized as the phobic stimulus is a crucial key feature of this disorder [4]. Germophobia is an irrational fear of germs [5].…”
Section: Introductionmentioning
confidence: 99%